Individuals’ perceptions of the factors linked to everyday soft drink consumption among university students: qualitative study - Sarhan, Mohammed Mahmoud; Aljohani, Shemaa Adel; Alnazzawi, Yara Ahmad; Alharbi, Nuorah Awadh; Alotaibi, Shihanah Eid; Alhujaili, Ahmed Saad; Alwadi, Maram Ali M. (Frontiers in Nutrition, 2024)
Soft drink consumption is continuing to grow worldwide, posing an increasing threat to people's health and general wellbeing. Consequently, we must understand the factors driving soft drink consumption to support improvements to nutrition. This paper adopts a qualitative research approach to explore individuals' perceptions of the factors linked to daily soft drink consumption among university students in Saudi Arabia.This research employed purposive sampling to recruit a total of 19 students attending university in Al Madinah Province, Saudi Arabia, all of whom reported that they had previously consumed soft drinks. Over three months, data was gathered through a mixture of online and in-person semistructured interviews. Once completed, the interviews were then transcribed and analyzed using inductive thematic analysis to identify the themes that emerged from the data.This study reveals five core themes: taste, habit, price, environment and social context, and health concerns. Regarding health concerns, this study finds that the public's increasing concerns about health can reduce people's consumption of soft drinks. Significantly, this research reveals that the rise in health concerns among the public is being driven by the growing conversation about healthy food and the negative impact of consuming sugary soft drinks occurring in wider society.To conclude, this research underlines the value of adopting a holistic approach to promoting healthier drink choices (and thus reducing soft drink consumption). Interventions that focus on factors associated with soft drink consumption, such as habits, price, environment, social settings, health concerns, and taste, will be better able to decrease soft drink consumption and improve people's nutritional intake.